Control strategy for stable formation of high‐speed virtually coupled trains with disturbances and delays. (17th June 2022) - Liu, Yafei; Zhou, Yang; Su, Shuai; Xun, Jing; Tang, Tao
Abstract: Virtual coupling (VC) brings unprecedented opportunities for the train operation system by controlling multiple trains as a virtually coupled train set (VCTS) via train automation and communication. To deal with communication delays and small disturbances in a VCTS, this paper developed a tube‐based control approach for the VCTS, focusing on optimizing the control performances and meanwhile guaranteeing the individual and string stability. Specifically, a tube model predictive control (MPC) framework is constructed to handle safety constraints and regulate bounded small disturbances. Then, the individual stability and string stability are ensured by designing the constraint sets for inputs and proper coefficient tuning within the stable region. Finally, simulation‐based experiments verify that the proposed approach shows better robustness and higher efficiency, which can regulate train states within a tube, and the VCTS can be asymptotically stable and string stable facing disturbances and delays.